Im Schatten Europas - Schnell, Florian (Germany, 2016)
In 2014, together with the journalist Elias Bierdel, a group of filmmakers involved in migration issues travel the external borders of the EU in an attempt to meet activists and refugees and give them a voice.
Verzio Film Festival Submission
Keywords: Documentary films